Two StereoTactic ablative radiotherapy treatments for localized prostate cancer (2STAR): Results from a prospective clinical trial. (June 2019) - Alayed, Yasir; Cheung, Patrick; Chu, William; Chung, Hans; Davidson, Melanie; Ravi, Ananth; Helou, Joelle; Zhang, Liying; Mamedov, Alexandre; Commisso, Angela; Commisso, Kristina; Loblaw, Andrew
Highlights: Two-fraction prostate SABR was very well tolerated with minimal late toxicity. The potential advantage is better QOL, particularly in the bowel and sexual domains. Early signals of efficacy (4yPSARR, PSA nadir and bDFS) are encouraging. Abstract: Purpose: Ultrahypofractionation is appealing for prostate cancer (PCa) due to low α/β, and increasing the dose per fraction could improve the therapeutic index. Here we report the outcomes of a phase II prostate SABR trial using two fractions. Methods: Patients had low or intermediate risk prostate cancer. Three gold fiducials were implanted for image guidance. The clinical target volume (CTV) included the prostate only, and the planning target volume (PTV) was a 3 mm expansion enabled through the use of a rectal immobilization device. The dose prescribed was 26 Gy in 2 weekly fractions (EQD2 110 Gy1.4 ). The primary endpoint was quality of life using EPIC, and minimal clinically important change (MCIC) was defined as an EPIC QOL decrease >0.5 SD. Results: 30 patients were accrued with a median follow-up of 49.3 months. 10% had low-risk, 33% had favourable intermediate-risk and 57% had unfavourable intermediate-risk PCa. Five patients received a short course of ADT. Median nPSA was 0.2 ng/ml. One patient had BF and is being observed. 56.6% of patients had a 4yPSARR. Six (20.7%) patients had a MCIC in the urinary domain, 6 (21.4%) had a MCIC in the bowel domain, and 3 (20%) had a MCIC in the sexual domain. Conclusions: Two-fraction SABR in prostate cancer is safe and feasible, with a minimal change in QOL and a low rate of late grade 3–4 toxicity. The PSA kinetics and biochemical control rates are encouraging given that the majority had unfavourable intermediate-risk disease, although longer follow-up is required.